Vocational education and training for development: a policy in need of a theory? - McGrath, Simon (Elsevier, 2012)
The current decade has seen a significant return of interest in vocational education and training (VET) amongst the international policy community. This rise in policy and programmatic interest in VET's role in development, however, stands in contrast to the state of the academic debate. Whilst there have continued to be both policy and academic developments in VET in OECD countries; in the South there has been a paucity of VET research and little in the way of theoretical exploration. Rather, the academic orthodoxy in the international education and development field is dismissive of VET's possible contribution. Given the return of the policy interest in VET for development, and the possibilities of a broader vision of education-development relations beyond 2015, when the MDGs end, it is time to revisit the role of VET in development from an explicitly theoretical stance. In this article, I argue that the current approach to VET is grounded in an outmoded model of development, whilst the academic critique of VET in developing countries is clearly long outdated. In contrast, I examine the implications for VET of recent trends in thinking about development through the exploration of three particular theoretical approaches: human rights, capabilities and integrated human development. I conclude by considering the purposes, natures and possibilities of VET as a means of human development.